Implementasi “Random Pairs Group” dalam pembelajaran Bahasa Arab Daring - Hisbullah Huda; Majidatun Ahmala (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2020)
The covid-19 pandemic forces students learning using digital media or called online learning. Lack of interaction between students when learning online makes lectures have to be creative and innovate in making learning more active and effective. Therefore, “Random Pairs Group” becomes a learning model that an increase interaction between students though they have not meet face to face at all member of class for one semester. Sp, the purpose of this study was to determine the implementation of the “random pairs group” in Arabic online learning. This research is a naturalstic qualitative research. Respondents of this study were intensive Arabic students of Tarbiyah faculty class N from group A and B, totaling 40 students. Data collection techniques were by observations, interviews, and documentation. The results of this study indicate that the Arabic learning process using “random pairs group” learning model is able to create positive interactions between students until the communication is created that builds students’ Arabic language skills